Preparation method and application of iodine-doped cobalt-based electrocatalyst
By using ammonium iodide for doping synchronous etching strategy in the electrocatalyst, the tandem catalytic active sites of cobalt single atoms and cobalt clusters are constructed, which solves the problem that existing electrocatalysts are difficult to achieve high ammonia yield and high Faraday efficiency at the same time during the synthesis of ammonia, and achieves efficient ammonia synthesis.
Patent Information
- Application Number
- CN202510061748.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
It is difficult for existing electrocatalysts to achieve high ammonia yield and high Faraday efficiency at the same time during the synthesis of ammonia, and there are serious competitive side reactions.
The mild ammonium iodide doping synchronous etching strategy was adopted to successfully anchor cobalt on an iodine-doped carbon substrate in the form of single atoms and clusters coexisting, and a tandem catalytically active site composed of iodine-coordinated cobalt single atoms and cobalt clusters was constructed.
The efficient promotion of the deoxygenation and hydrogenation steps in the electrocatalytic nitrate reduction reaction was achieved, and the electrocatalytic synthesis of ammonia showed ammonia yields of more than 17000 μg h-1 mgcat.-1 and Faraday efficiency greater than 95%.
Smart Images

Figure CN119876996A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic ammonia synthesis catalysts, and specifically relates to an iodine-doped cobalt-based electrocatalyst and a preparation method thereof. Background Art
[0002] Ammonia is an extremely important compound and is widely used in industries such as industry, agriculture, and energy. Currently, the industry relies on the Haber-Bosch process for large-scale ammonia synthesis. The harsh reaction conditions (350-500°C, 20-50Mpa) will lead to the emission of about 300 million tons of carbon dioxide each year and consume about 2% of the world's energy. Therefore, it is necessary to explore more environmentally friendly and sustainable methods for ammonia synthesis. Recently, electrocatalytic technology using renewable energy electricity, nitrogen-containing species and water as driving force, nitrogen source and proton source respectively has shown great application potential in the field of ammonia synthesis. As a pollutant widely present in wastewater, nitrate has a higher solubility in aqueous solution and is more easily broken N=O bond (204kJ mol -1 ) can effectively improve the reaction kinetics of electrocatalytic synthesis of ammonia. Therefore, the electrocatalytic nitrate reduction reaction can convert nitrate pollutants into ammonia with higher added value under ambient conditions, which is conducive to obtaining valuable chemicals while solving environmental pollution problems.
[0003] Since the electrocatalytic nitrate reduction reaction involves complex deoxygenation and hydrogenation processes, the design of the electrocatalyst determines the yield and Faraday efficiency of its ammonia synthesis. At present, relevant technologies for preparing electrocatalysts for electrocatalytic reduction of nitrates to synthesize ammonia have been reported. Patent CN118880375A discloses a Ti3C2T x Ti3C2T prepared with copper nitrate as raw materials x The yield of nitrate reduction to ammonia by the NENU-3 composite catalyst reached 16370 μg h -1 mg cat. -1 , but the Faraday efficiency is only 79.49%, which indicates that serious competitive side reactions occurred in the process of synthesizing ammonia; Patent CN118407081A discloses a nickel foam-supported copper-molybdenum nanocrystalline alloy catalyst, which exhibits a Faraday efficiency of 98.9%, but the ammonia yield is only 479.2 μmol h -1 cm -2 (8150 μg h -1 cm -2 ), which seriously affects the further practical application of the catalyst.
[0004] Therefore, designing and preparing an electrocatalyst with both high ammonia yield and high Faradaic efficiency is of great significance for sustainable and efficient ammonia synthesis. Summary of the invention
[0005] The purpose of the present invention is to address the limitations of current technologies and to provide a method for preparing and applying an iodine-doped cobalt-based electrocatalyst. The method uses a mild ammonium iodide doping and synchronous etching strategy to successfully anchor cobalt in the form of single atoms and clusters on an iodine-doped carbon substrate in one step; the resulting iodine-doped cobalt-based electrocatalyst has a series of catalytic active sites composed of iodine-coordinated cobalt single atoms and cobalt clusters, which can simultaneously promote the deoxygenation and hydrogenation steps in the electrocatalytic nitrate reduction reaction. The electrocatalytic synthesis of ammonia obtained by the present invention exhibits a yield of more than 17,000 μg h -1 mg cat. -1 The ammonia yield and Faraday efficiency of more than 95% achieve both high ammonia yield and high Faraday efficiency, providing a new idea for green, efficient and sustainable ammonia synthesis.
[0006] The technical solution of the present invention is:
[0007] A method for preparing an iodine-doped cobalt-based electrocatalyst, the method comprising the following steps:
[0008] (1) mixing a methanol solution containing 2-methylimidazole and a methanol solution containing cobalt nitrate hexahydrate for 30 to 45 minutes, and then standing and aging for 2 to 5 hours, and then centrifuging, washing and vacuum drying to obtain a purple precursor, namely ZIF-67;
[0009] Wherein, the mass ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:1 to 1.5;
[0010] (2) placing the dried purple precursor in a tube furnace filled with Ar atmosphere for pyrolysis at 700-800 °C and maintaining for 3-5 h to obtain a black powder, i.e., Co nanoparticles anchored on a carbon substrate (Co NP / C);
[0011] (3) Co NP / C and ammonium iodide are placed in the downstream and upstream of a tube furnace, respectively, and pyrolyzed at 700-800° C. in an argon gas atmosphere and maintained for 1-3 hours to obtain an iodine-doped cobalt-based electrocatalyst.
[0012] The mass ratio is Co NP / C: ammonium iodide = 1:20 to 25. The heating rate is 1 to 5°C / min.
[0013] In the methanol solution of cobalt nitrate hexahydrate, 400-500 mg of cobalt nitrate hexahydrate is added per 40 mL of methanol;
[0014] In the methanol solution of 2-methylimidazole, 400-750 mg of 2-methylimidazole is added per 20 mL of methanol.
[0015] The iodine-doped cobalt-based electrocatalyst prepared by the method is used for electrocatalytic reduction of nitrate to synthesize ammonia.
[0016] Specifically, the steps include: in a three-electrode system, electrolyzing the electrolyte for 1 to 2 hours by a constant voltage method to obtain ammonia;
[0017] Among them, in the three-electrode system, platinum sheet, Ag / AgCl and carbon paper loaded with iodine-doped cobalt-based electrocatalyst are respectively used as counter electrode, reference electrode and working electrode; the electrolytic cell type is H-type electrolytic cell, and the diaphragm is Nafion 117 membrane; the electrolyte is composed of 0.1-0.5M K2SO4 solution containing 0.1-0.5M KNO3;
[0018] In the working electrode, 0.5 to 1 mg of catalyst is loaded per 1 square centimeter of carbon paper;
[0019] The voltage range of electrolysis is -0.3V to -0.8V.
[0020] The essential features of the present invention are:
[0021] The present invention constructs a series catalytic active site of cobalt single atoms and cobalt clusters coordinated by iodine, thereby simultaneously promoting the deoxygenation and hydrogenation steps of the electrocatalytic reduction of nitrates, and uses mild ammonium iodide to carry out a doping synchronous etching strategy, which can complete the doping and etching that originally required two steps in one step. During the pyrolysis process, ammonium iodide acts as both an etchant and a dopant. Specifically, the iodine vapor released by the decomposition of ammonium iodide will not only achieve heteroatom doping by forming a CI bond with a carbon substrate, but also react with excess cobalt nanoparticles to form volatile cobalt iodide and escape from the catalyst with the airflow, thereby preparing an electrocatalyst (Co SAAC / IC) in which cobalt single atoms and cobalt clusters coexist on iodine-doped carbon; it can promote the deoxygenation and hydrogenation processes in the process of synthesizing ammonia by electrocatalytic reduction of nitrates, thereby simultaneously achieving high ammonia yield and high Faraday efficiency.
[0022] The present invention has the following beneficial effects:
[0023] 1. The electrocatalyst preparation of the present invention can achieve doping of the carbon substrate and etching of the cobalt metal nanoparticles in one step only through a mild ammonium iodide thermal decomposition process.
[0024] 2. The present invention cleverly constructs a series of catalytic active sites where iodine-doped cobalt single atoms and cobalt clusters coexist through a mild doping synchronous etching strategy, which can efficiently promote the deoxygenation and hydrogenation processes in the electrocatalytic reduction of nitrates, thereby not only improving the yield of electrocatalytic synthesis of ammonia, but also improving the Faraday efficiency.
[0025] 3. Due to the coordination of iodine atoms on single cobalt atoms, the electrocatalytic nitrate reduction reaction is transformed from a single adsorption mechanism to a tandem catalytic mechanism, thereby effectively improving the performance of electrocatalytic ammonia synthesis.
[0026] 4. The iodine-doped carbon structure in which single cobalt atoms and cobalt clusters coexist can be obtained by the doping and simultaneous etching strategy of ammonium iodide. Among them, the cobalt single atoms coordinated by iodine change from the original favorable adsorption of water and hydrogen to the favorable adsorption of nitrate, thereby driving the transformation of the electrocatalytic nitrate reduction reaction from a single adsorption mechanism to a tandem catalytic mechanism. The adjacent cobalt clusters can provide abundant active hydrogen for the subsequent hydrogenation step by accelerating the dissociation of water, thereby constructing a tandem catalytic active site with the cobalt single atoms coordinated by iodine to promote the electrocatalytic nitrate reduction reaction.
[0027] 5. Thanks to the mechanism transformation caused by iodine doping and the construction of tandem catalytic active sites, the iodine-doped cobalt-based electrocatalyst also showed a high ammonia yield (17790 μg h -1 mg cat. -1 ) and high Faraday efficiency (96.8%). The ammonia yield of the iodine-doped cobalt-based electrocatalyst prepared by the present invention exceeds 17 mg h -1 mg cat. -1 , and the Faradaic efficiency is greater than 95%, which can simultaneously reach the high level of the reported synthetic ammonia electrocatalysts, which provides new inspiration for the preparation of synthetic ammonia electrocatalysts with serial catalytic active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the electrocatalyst prepared in Example 1.
[0029] Figure 2 This is a transmission electron microscope image of the electrocatalyst prepared in Example 1.
[0030] Figure 3 This is a spherical aberration corrected transmission electron microscope image of the electrocatalyst prepared in Example 1.
[0031] Figure 4 X-ray diffraction patterns of the electrocatalysts prepared in Examples 1, 2, and 3.
[0032] Figure 5 This is the near-edge X-ray absorption fine structure spectrum of the electrocatalyst prepared in Example 1.
[0033] Figure 6 This is the extended edge X-ray absorption fine structure spectrum of the electrocatalyst prepared in Example 1.
[0034] Figure 7Linear sweep voltammetry curves of the electrocatalysts prepared in Examples 1, 2 and 3 in an electrolyte.
[0035] Figure 8 The yield of ammonia synthesis of the electrocatalysts prepared in Examples 1, 2 and 3.
[0036] Fig. 9 The Faraday efficiency of ammonia synthesis of the electrocatalysts prepared in Examples 1, 2, and 3. DETAILED DESCRIPTION
[0037] The specific implementation steps and drawings of the present invention are described in full and clearly below. It is necessary to point out that the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, other embodiments or inferences obtained without making innovative ideas should be considered to belong to the protection scope of the present invention.
[0038] Embodiment 1:
[0039] The specific preparation method of iodine-doped cobalt-based electrocatalyst is as follows:
[0040] (1) 450 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 40 mL of methanol and stirred for 30 minutes to obtain a methanol solution containing Co(NO3)2·6H2O.
[0041] (2) 500 mg of 2-methylimidazole was dissolved in 20 mL of methanol and ultrasonicated for 30 minutes to obtain a methanol solution containing 2-methylimidazole.
[0042] (3) The above-obtained methanol solution containing Co(NO3)2·6H2O and the methanol solution containing 2-methylimidazole were mixed and stirred for 30 minutes, and then allowed to stand for 4 hours, and then centrifuged, washed and vacuum dried to obtain a ZIF-67 precursor.
[0043] (4) ZIF-67 was placed in a tube furnace filled with Ar atmosphere and heated to 800 °C at a rate of 2 °C / min and maintained for 3 h to obtain cobalt nanoparticles supported on a carbon substrate (Co NP / C).
[0044] (5) 1 g of Co NP / C and 25 g of ammonium iodide were placed in the downstream and upstream of the tube furnace, respectively. In an Ar atmosphere with a gas flow rate of 40 scm, the mixture was heated to 800 °C at a rate of 10 °C / min and maintained for 1 hour, followed by natural cooling to obtain an electrocatalyst in which cobalt single atoms and cobalt clusters coexisted on iodine-doped carbon (Co SAAC / IC).
[0045] The morphology of Co SAAC / IC was observed using a scanning electron microscope (SEM). Figure 1 As shown, the Co SAAC / IC exhibits a slightly wrinkled rhombic dodecahedral structure, and no obvious cobalt nanoparticles are observed.
[0046] Transmission electron microscopy (TEM) was used to analyze the morphology and structure of Co SAAC / IC. Figure 2 As shown, no aggregation of cobalt nanoparticles was observed at high resolution, which indicates that excess cobalt nanoparticles were successfully etched away by ammonium iodide.
[0047] The existence form of cobalt in Co SAAC / IC was further observed using spherical aberration-corrected transmission electron microscopy (AC-TEM). Figure 3 As shown in Figure 2, the coexistence of a large number of cobalt single atoms and cobalt clusters can be clearly observed, where the bright spots in the dashed circle and the solid circle represent cobalt single atoms and cobalt clusters, respectively. It is worth noting that the cobalt clusters are almost surrounded by cobalt single atoms, indicating that there may be a synergistic effect between the two.
[0048] The phase composition of Co SAAC / IC was analyzed by X-ray diffraction (XRD). Figure 4 Only a broad diffraction peak at 26° was observed, which represents the (002) plane of carbon. No diffraction peaks related to metallic cobalt were observed, which proves the atomically dispersed form of cobalt species.
[0049] The electronic structure and valence state of cobalt species in Co SAAC / IC were analyzed by near-edge X-ray absorption fine structure spectroscopy (XANES). Figure 5 As shown, the near-edge absorption energy of cobalt in Co SAAC / IC is between that of cobalt foil and cobalt oxide, indicating that the valence state is between 0 and + 2. In addition, in the range of 7730-7780 eV, Co SAAC / IC presents a nearly flat feature, corresponding to the joint contribution of cobalt single atoms and cobalt clusters.
[0050] The coordination environment of cobalt species in Co SAAC / IC was analyzed using extended edge X-ray absorption fine structure spectroscopy (EXAFS). Figure 6 As shown, Co SAAC / IC The characteristic peak at the same position as the first main peak of cobalt phthalocyanine is shown, which indicates the existence of cobalt single atomic structure. The characteristic peak at is at the same position as the main peak of cobalt foil, which proves the existence of cobalt clusters.
[0051] The electrocatalytic performance of Co SAAC / IC was studied by linear sweep voltammetry. Figure 7 As shown in Figure 2, Co SAAC / IC exhibits the lowest overpotential (135.1 mV) and the highest current density (89.53 mA cm-2 ), which indicates that Co SAAC / IC has excellent electrocatalytic activity, thus demonstrating that the tandem catalytic active sites are crucial for promoting the electrocatalytic nitrate reduction reaction.
[0052] The specific steps include: (1) using a three-electrode system on a Shanghai Chenhua CHI-760E electrochemical workstation to conduct an electrolytic experiment of electrocatalytic reduction of nitrate to synthesize ammonia, wherein platinum sheet, Ag / AgCl, and an area of 1 cm 2 The carbon paper-supported catalyst was used as the counter electrode, reference electrode and working electrode respectively. (2) The electrolysis test was carried out in an H-type electrolytic cell separated by a Nafion 117 membrane, which contained an electrolyte of 0.1M KNO3 and 0.5M K2SO4. The Nafion 117 membrane was pretreated by first treating it in a 5wt% H2O2 solution at 80°C for 1 hour and soaking it in deionized water for 30 minutes, and then soaking it in H2SO4 at 80°C for 1 hour and soaking it in deionized water at 80°C for 30 minutes. (3) The preparation steps of the working electrode are as follows: 10 mg of the catalyst was dispersed in a mixed solution (50μL Nafion solution + 0.45mL deionized water + 0.45mL anhydrous ethanol) and ultrasonically treated for half an hour to form a uniform ink. 50μL of the catalyst ink was dropped on a 1cm 2 on carbon paper and dried naturally. (4) All electrolysis potentials involved in this work are reversible hydrogen electrode (RHE) potentials, and the conversion formula is E(RHE)=E(Ag / AgCl)+0.059×pH+0.197. (5) The electrocatalyst was subjected to a chronoamperometric test for 1 hour at different electrolysis potentials, and the electrolysis potential range was -0.3V to -0.8V. (6) After the chronoamperometric test, 2mL of electrolyte was taken out and the ammonia synthesized by the electrocatalyst was qualitatively and quantitatively analyzed by UV spectrophotometer.
[0053] The amount of ammonia synthesis in the electrolyte of Co SAAC / IC after electrolysis under the chronoamperometry was detected using an ultraviolet spectrophotometer. Figure 8 As shown in Figure 2, the Co SAAC / IC achieved an ammonia yield of 17790 μg h at an applied voltage of −0.6 V. - 1 mg cat. -1 , which makes sustainable and large-scale ammonia synthesis possible. Figure 8 The Co SAAC / IC, Co NP / C and CoSA / IC involved in the test were all tested on a CHI-760E electrochemical workstation using a three-electrode system. The three-electrode system is composed of a platinum sheet, Ag / AgCl, and an area of 1 cm 2The carbon paper-supported catalyst was used as the counter electrode, reference electrode and working electrode respectively. The electrolysis test method adopted the chronoamperometry. The applied voltage range was -0.3V to -0.8V (constant voltage). The composition of the electrolyte was 0.5M K2SO4 electrolyte containing 0.1M KNO3. The instrument for measuring the ammonia yield after electrolysis was a UV spectrophotometer.
[0054] The corresponding Faradaic efficiency was calculated using the ammonia yields obtained by Co SAAC / IC at different voltages. Fig. 9 As shown, the Faradaic efficiency of Co SAAC / IC remains above 80% within the voltage range of electrolysis and is as high as 96.8% at an applied voltage of -0.6 V, which proves that it can improve the selectivity of the electrocatalytic reduction of nitrate to synthesize ammonia by inhibiting the occurrence of competitive side reactions.
[0055] Example 2
[0056] The other steps are the same as those in Example 1, except that step (5) of Example 1 is omitted, and the obtained sample is cobalt nanoparticles supported on a carbon substrate (Co NP / C);
[0057] The phase composition of Co NP / C was analyzed using X-ray diffraction patterns. Figure 4 As shown, a typical broad peak is displayed at 26°, which represents the (002) plane of carbon; three obvious sharp characteristic peaks are shown at 44.9°, 52.5° and 76.6°, which are respectively attributed to the (111), (200) and (220) crystal planes of cobalt, indicating the large-scale aggregation of cobalt nanoparticles on the carbon substrate.
[0058] The electrocatalytic performance of Co NP / C was analyzed by linear sweep voltammetry. Figure 7 As shown, the current density of Co NP / C at each potential is smaller than that of Co SAAC / IC, indicating that the electrocatalytic activity of Co NP / C for nitrate reduction to ammonia is lower than that of Co SAAC / IC.
[0059] The amount of ammonia synthesis in the electrolyte after electrolysis of Co NP / C at different constant voltages was detected using an ultraviolet spectrophotometer. Figure 8 As shown in Figure 2, the ammonia yield of Co NP / C was 9535 μg h at an applied voltage of −0.6 V. -1 mg cat. -1 .
[0060] The Faradaic efficiency was calculated using the ammonia yield of Co NP / C electrocatalyst at different voltages. Fig. 9As shown, the Co NP / C electrocatalyst exhibited a Faradaic efficiency of 72% at an applied voltage of −0.6 V.
[0061] The ammonia yield and Faradaic efficiency of Co NP / C at an applied voltage of −0.6 V were 9535 μg h -1 mg cat. -1 and 72%, both lower than Co SAAC / IC. Due to the lack of the synchronous etching step of ammonium iodide doping, the Co NP / C lacks the single-atom structure doped with iodine, which is not conducive to the deoxygenation process of the catalyst in the electrocatalytic nitrate reduction reaction, thereby reducing the overall performance of the electrocatalytic synthesis of ammonia.
[0062] Example 3
[0063] The other steps are the same as those in Example 1, except that step (6) is added after step (5) in Example 1, the Co SAAC / IC obtained in step (5) in Example 1 is dispersed in a HCl solution and stirred for 24 hours, then the acid solution is washed with deionized water until it is neutral, and finally freeze-dried to obtain a sample of cobalt single atoms supported on iodine-doped carbon (Co SA / IC).
[0064] Co SA / IC was analyzed using X-ray diffraction patterns. Figure 4 As shown, only a broad characteristic diffraction peak at 26° attributed to carbon was observed, and no diffraction peak related to metallic cobalt was observed, which proves that the cobalt species exists in an atomically dispersed form.
[0065] The electrocatalytic performance of Co SA / IC was analyzed by linear sweep voltammetry. Figure 7 As shown, the current density of Co SA / IC at each potential is smaller than that of Co SAAC / IC, indicating that the activity of Co SA / IC electrocatalyst for electrocatalytic reduction of nitrate to synthesize ammonia is lower than that of Co SAAC / IC.
[0066] The amount of ammonia synthesis in the electrolyte after electrolysis of Co SA / IC at different constant voltages was detected using an ultraviolet spectrophotometer. Figure 8 As shown in Figure 2, the Co SA / IC electrocatalyst has an ammonia yield of 6375 μg h at an applied voltage of −0.6 V. -1 mg cat. -1 .
[0067] The Faradaic efficiency was calculated using the ammonia yield of the Co SA / IC electrocatalyst at different voltages. Fig. 9 As shown, the Faradaic efficiency of Co SA / IC is only 58% at an applied voltage of -0.6 V.
[0068] The ammonia yield and Faradaic efficiency of Co SA / IC at an applied voltage of −0.6 V were 6375 μg h -1 mg cat. -1 and 58%, which is far inferior to Co SAAC / IC. Under HCl solution immersion, the cobalt clusters in Co SAAC / IC will be removed by acid washing to obtain Co SA / IC with only iodine-doped cobalt single atoms. Therefore, the reason for the performance degradation of Example 3 is that the lack of cobalt clusters slows down the hydrogenation step in the electrocatalytic nitrate reduction reaction, thereby limiting the conversion of reaction intermediates to the final product ammonia.
[0069] Example 4
[0070] The other steps are the same as those in Example 1, except that the mass of 2-methylimidazole in step (4) of Example 1 is replaced by 600 mg from 500 mg;
[0071] The obtained material properties are close;
[0072] Example 5
[0073] The other steps are the same as those in Example 1, except that the annealing temperature in step (4) of Example 1 is replaced by 700° C. from 800° C.;
[0074] The obtained material properties are close;
[0075] Example 6
[0076] The other steps are the same as those in Example 1, except that the mass of ammonium iodide in step (5) of Example 1 is replaced by 20 g from 25 g;
[0077] The obtained material properties are close;
[0078] Example 7
[0079] The other steps are the same as those in Example 1, except that the pyrolysis time in step (5) of Example 1 is replaced from 1 hour to 3 hours;
[0080] The obtained material properties are close;
[0081] In summary, the electrocatalyst prepared by the present invention solves the problem that the current electrocatalysts for synthesizing ammonia cannot have both high yield and high Faraday efficiency. As an efficient electrocatalyst for synthesizing ammonia, Co SAAC / IC has tandem catalytic active sites that can simultaneously promote the deoxygenation and hydrogenation processes in the electrocatalytic nitrate reduction reaction. Thanks to the mechanism transformation induced by iodine doping and the tandem catalytic effect between cobalt single atoms and cobalt clusters, Co SAAC / IC has both high ammonia yield and high Faraday efficiency in the electrocatalytic nitrate reduction reaction, which provides the possibility for efficient and sustainable development of electrocatalytic ammonia synthesis.
[0082] The above contents are only examples and explanations of the concept of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
[0083] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing an iodine-doped cobalt-based electrocatalyst, characterized in that: The method comprises the following steps: (1) mixing a methanol solution containing 2-methylimidazole and a methanol solution containing cobalt nitrate hexahydrate, stirring for 30 to 45 minutes, standing for 2 to 5 hours, and then centrifuging, washing and vacuum drying to obtain a purple precursor, namely ZIF-67; Wherein, the mass ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:1 to 1.5; (2) placing the dried purple precursor in a tube furnace filled with Ar atmosphere for pyrolysis at 700-800 °C and maintaining for 3-5 hours to obtain a black powder, Co NP / C; (3) placing Co NP / C and ammonium iodide in the downstream and upstream of a tube furnace, respectively, and pyrolyzing them at 700-800° C. in an argon gas atmosphere and maintaining the temperature for 1-3 hours to obtain an iodine-doped cobalt-based electrocatalyst; The mass ratio is Co NP / C:ammonium iodide=1:20-25.
2. The method for preparing an iodine-doped cobalt-based electrocatalyst according to claim 1, characterized in that: In the methanol solution of cobalt nitrate hexahydrate, 400-500 mg of cobalt nitrate hexahydrate is added per 40 mL of methanol; In the methanol solution of 2-methylimidazole, 400-750 mg of 2-methylimidazole is added per 20 mL of methanol.
3. The method for preparing an iodine-doped cobalt-based electrocatalyst according to claim 1, characterized in that: The heating rate is 1-5°C / min.
4. A method for applying the iodine-doped cobalt-based electrocatalyst prepared by the method of claim 1, characterized in that: Used for electrocatalytic reduction of nitrate to synthesize ammonia.
5. The application method as claimed in claim 4, characterized in that: The method comprises the following steps: electrolyzing the electrolyte for 1 to 2 hours by a constant voltage method in a three-electrode system to obtain ammonia; Among them, in the three-electrode system, platinum sheet, Ag / AgCl and carbon paper loaded with iodine-doped cobalt-based electrocatalyst are respectively used as counter electrode, reference electrode and working electrode; the electrolytic cell type is H-type electrolytic cell, and the diaphragm is Nafion 117 membrane; the electrolyte is composed of 0.1-0.5M K2SO4 solution containing 0.1-0.5M KNO3; In the working electrode, 0.5 to 1 mg of catalyst is loaded per 1 square centimeter of carbon paper; The voltage range of electrolysis is -0.3V to -0.8V.
Citation Information
Patent Citations
Cobalt monatomic loaded nitrogen-doped carbon oxygen reduction catalyst and preparation method thereof
CN111468167A
Three-dimensional Co-doped WP2 nanosheet array electrocatalyst and preparation method thereof
CN111514912A
High-stability zinc-iodine battery positive electrode composite material as well as preparation method and application thereof
CN113036144A
Iodine-doped derivative porous carbon composite material and preparation method thereof
CN114132915A
Preparation method of electron coupling type cobalt-gold nitrogen doped porous carbon catalyst and product and application of electron coupling type cobalt-gold nitrogen doped porous carbon catalyst
CN117165962A
Cited By
Electro-catalysis water treatment system capable of realizing self-supply
CN120383370A